Selling and sales management - Jobber, David; Lancaster, Geoffrey (Pearson, 2015)
This new edition comes fully updated with new case studies, using working businesses to connect sales theory to the practical implications of selling in a modern environment. This edition contains the results from cutting-edge research that differentiates it from most of its competitors. The book continues to place emphasis on global aspects of selling and sales management. Topics covered include technological applications of selling and sales management, ethics of selling and sales management, systems selling and a comprehensive coverage of key account management.
Keywords: Sales management; Selling; Sales promotion; myyntityö; myynti; myynninedistäminen; markkinointi; yritysstrategiat; strategiat; digitaalinen markkinointi; budjetointi